Mosquito control workers in Malaysia: is lifetime occupational pesticide exposure associated with poorer neurobehavioral performance? - Yusof, Muhammad Zubir; Cherrie, John W.; Samsuddin, Niza; Semple, Sean (Oxford University Press, 2022)
Use of pesticides has been linked to neurobehavioral deficits among exposed workers. In Malaysia, organophosphate and pyrethroid pesticides are commonly used to control mosquito-borne diseases. This study aims to assess workers’ lifetime occupational pesticide exposure and examine the relationship with neurobehavioral health. A cross-sectional study was conducted on 158 pesticide-exposed and 176 non-exposed workers. To collect historical exposure and job tasks, a questionnaire and an occupational history interview were used. Pesticide exposure was measured in a subgroup of workers via inhalation and skin contact. The total pesticide intake of each worker was assessed using inhalation and dermal exposure models. CANTAB® computerised neurobehavioral performance assessments were used. The participants’ mean age was 31 (8) years. Pirimiphos-methyl (median = 0.569 mg/m3, Interquartile range [IQR] = 0.151, 0.574) and permethrin (median = 0.136 mg/m3, IQR = 0.116, 0.157) had the highest measured personal inhalation concentrations during thermal spraying. The estimated total lifetime pesticide intake for exposed workers ranged from 0.006 g to 12800 g (median = 379 g and IQR = 131, 794 g). Dermal exposure was the predominant route of pesticide intake for all workers. Compared to controls, workers with high lifetime pesticide intake had lower Match to Sample Visual (adjusted B = −1.4, 95% Confidence Interval (CI) = −2.6, 0.1), Spatial Recognition Memory (adjusted B = −3.3, 95% CI = −5.8, 0.8), Spatial Span (SSP) (adjusted B = −0.6, 95% CI = −0.9, 0.3) scores. Workers with low pesticide intake performed worse than controls (adjusted B = −0.5, 95% CI = −0.8, −0.2) in the SSP test, but scored higher in the Motor Screening test (adjusted B = 0.9, 95% CI = 0.1, 1.6). Higher Paired Associates Learning test scores were observed among higher (adjusted B = 7.4, 95% CI = 2.3, 12.4) and lower (adjusted B = 8.1, 95% CI = 3, 13.2) pesticide intake groups. There was no significant difference between the Reaction Time and Pattern Recognition Memory tests with lifetime pesticide intake after adjusting for confounders. Pesticide exposure has been linked to poorer neurobehavioral performance. As dermal exposure accounts for a major fraction of total intake, pesticide prevention should focus on limiting dermal exposure.